2004
DOI: 10.1128/aac.48.6.2014-2020.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voriconazole on Cryptococcus neoformans

Abstract: Voriconazole is a broad-spectrum triazole that offers extended activity against molds and yeasts that are not susceptible to earlier azole-type drugs. Recent studies indicate that melanization can severely reduce the susceptibility of certain antifungal drugs, but there is no information as to whether voriconazole is vulnerable to this effect. The activity of voriconazole on C. neoformans was assessed by MIC analysis and time-kill assays for melanized and nonmelanized cells. Cell morphology, capsule release, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…Although standard MIC susceptibility testing did not show any differences between the strains, the strains that produced melanin in the presence of L-DOPA were significantly more resistant to killing by AMB than the albino isolates. This finding is consistent with prior publications, reporting that time-kill experiments reveal that C. neoformans melanization is protective against AMB (18,41,42). Melanotic C. neoformans strains have been reported to be more virulent in animal models than melaninlacking strains (23).…”
Section: Discussionsupporting
confidence: 92%
“…Although standard MIC susceptibility testing did not show any differences between the strains, the strains that produced melanin in the presence of L-DOPA were significantly more resistant to killing by AMB than the albino isolates. This finding is consistent with prior publications, reporting that time-kill experiments reveal that C. neoformans melanization is protective against AMB (18,41,42). Melanotic C. neoformans strains have been reported to be more virulent in animal models than melaninlacking strains (23).…”
Section: Discussionsupporting
confidence: 92%
“…As reported previously (Yildiran et al, 2000;van Duin et al, 2004;Souza et al, 2005;Khan et al, 2007), voriconazole exhibited the highest inhibitory activity against the isolates of C. neoformans var. grubii (GM 0.056 mg ml 21 ) and C. gattii (GM 0.138 mg ml 21 ).…”
Section: Discussionsupporting
confidence: 58%
“…Previous reports indicated that the polysaccharide capsule of C. neoformans in the brain is smaller than in the lung in a murine model of cryptococcosis (51), a finding that we could not confirm in this study. We also could not document a significant decrease in capsule size in sequential isolates pre-and posttreatment, although this had been shown in both in vitro (56) and in vivo (J. D. Nosanchuk, personal communication) studies.…”
Section: Discussionmentioning
confidence: 64%